Art pedagogy in the development of creative abilities of preschool children (Journal of Educational Sciences, 2025)
With the advancement of society and the increasing demand for creative individuals, the relevance of developing creative abilities through art technologies has gained significant importance. This article explores the specific characteristics and potential of art pedagogy in fostering creative capacities within the educational and pedagogical processes of preschool institutions. Special emphasis is placed on the early implementation of art technologies, which enhances the effective identification and development of children's creative potential and facilitates their successful socialization. Art pedagogy is presented as a progressive and promising approach in contemporary education, aligning with modern educational standards that prioritize active learner participation. The article provides a theoretical analysis of the key concepts such as "art pedagogy," "creativity," "imagination," and "creative imagination," elucidating their underlying principles. Additionally, the methodological foundations for the application of art pedagogy, tailored to the age-specific needs of preschool children, are examined based on the author’s practical experience. 90 children took part in the experimental work. The study further elaborates on the role and significance of art pedagogy in the development of creative abilities and offers methodological recommendations relevant to this domain. Key words: creativity, imagination, artistic pedagogy.